2006
DOI: 10.1038/labinvest.3700387
|View full text |Cite
|
Sign up to set email alerts
|

Detection of single nucleotide polymorphisms by minisequencing on a polypyrrole DNA chip designed for medical diagnosis

Abstract: With the increasing availability of genetic information and its relationship to human diseases, there is a growing need in the medical diagnostic field for technologies that can proceed to the parallel genotyping of multiple markers. In this paper, we report the development of a new flexible microarray-based method that aims to be inexpensive, accurate, and adapted to routine analysis. The construction of the MICAM s (MICrosystem for Analysis in Medicine) DNA chip is based on the controlled electrosynthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Detecting known and unknown mutations is a major task in gene mutation detection (Butler et al, 2001). With the rapid development of molecular biology technology, more and more new technologies, such as DNA chip (Ho-Pun-Cheung et al, 2006;Kim et al, 2004;Vernet and Tran, 2005) and DHPLC (Lilleberg, 2003;Ribas et al, 2001) are used in this field. These new technologies can improve the efficiency and accuracy in mutation detection, but many special instruments and software are required which limits its generalization in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting known and unknown mutations is a major task in gene mutation detection (Butler et al, 2001). With the rapid development of molecular biology technology, more and more new technologies, such as DNA chip (Ho-Pun-Cheung et al, 2006;Kim et al, 2004;Vernet and Tran, 2005) and DHPLC (Lilleberg, 2003;Ribas et al, 2001) are used in this field. These new technologies can improve the efficiency and accuracy in mutation detection, but many special instruments and software are required which limits its generalization in many fields.…”
Section: Introductionmentioning
confidence: 99%
“…Microarrays represent an inexpensive and accurate tool for parallel genotyping of multiple markers, suitable for routine analysis in medical diagnostics [13]. Here, we report on the development of a highly sensitive microarray for the detection of KRAS and BRAF mutations.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Therefore, great efforts have been taken to develop convenient, sensitive, and selective genotyping methods for the detection of SNPs, [5][6][7] with the hope of rapid and reliable genetic analysis of diseases and subtle genetic risk factors. [7][8][9][10][11] Several elegant strategies for SNP interrogation have been proposed, 6 including allele-specific oligonucleotide (ASO) hybridization, 12 oligonucleotide ligation assays (OLA), 8,[13][14][15][16][17] and primer extension assays, 10,11 relying on various physical readout such as optical, [12][13][14]18 electrochemical, 15,[19][20][21][22] and mechanical techniques. 23 Because of their inherent attractive properties of high sensitivity with minimal power/cost/mass requirements, [24][25][26] electrochemical DNA sensors have attracted significant research interest and shown great promise in SNP genotyping.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of DNA sequence variation has important implications in molecular genetics, such as the linkage and association analysis of disease genes, genetic vulnerability toward diseases, and legal medical applications to identify criminals . Single-nucleotide polymorphisms (SNPs) are the most prevalent and stably inherited types of sequence variations in the human genome and have been widely regarded as promising disease markers. , Therefore, great efforts have been taken to develop convenient, sensitive, and selective genotyping methods for the detection of SNPs, with the hope of rapid and reliable genetic analysis of diseases and subtle genetic risk factors. …”
Section: Introductionmentioning
confidence: 99%